EMISIÓN DIFUSA DE HIDRÓGENO EN EL VOLCÁN POÁS, COSTA RICA - Melián, Gladys V. (2011)
We report the results of the study of diffuse H2 emission from Poás volcano, Costa Rica. Three surveys were carried out in 2000, 2001 and 2002, to investigate soil H2 distribution in and around Poás summit crater and to evaluate diffuse H2 emission as a potential geochemical tool for the Poás volcano monitoring program. Soil H2 contents showed a wide range of concentrations from 0.4 to 7,059 ppmV. Most of the study area showed low levels of H2 in the soil atmosphere, and the highest values of soil gas H2 were just observed inside the summit crater of Poás volcano for the 2001 and 2002 surveys. These surface geochemical changes coincide with an increase of the fumarolic activity as well as soil temperature rose inside the crater during this study.The results here reported suggest changes in the Poás volcanic-hydrothermal system, therefore monitoring diffuse H2 emission could be useful for the volcanic surveillance of Poás volcano.